Methodology Of Solving Problems from Physics and Solutions in Secondary Schools - Karasakalov Revkat Kenesovich (Genius Publishing Group, 2022)
The article develops a methodology for solving problems related to isothermal processes in physics in secondary schools
Keywords: mental; school; isothermal; isobaric